2022
DOI: 10.1038/s41598-022-18881-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of saltmarsh systems in estuarine trapping of microplastics

Abstract: Saltmarshes are important natural ecosystems along many temperate (and other) coastlines. They stabilize sediments and act as biofilters for a range of industrial pollutants and, potentially, microplastics. Accumulation of microplastics along estuarine coastlines may be enhanced by the presence of saltmarsh species, as they offer better particle trapping efficiency than adjacent intertidal mudflats under prevailing flood and ebb tidal currents. However, the trapping efficiency of entire saltmarsh systems under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Otherwise, variability in mp/MeP concentration may be consequent to the dynamic nature of estuaries, with the influence of tidal fluctuations, water circulation patterns, infauna burrowing activity, shoreline topography, pollution events and frequencies that may regulate the resuspension, dispersion and settling of plastics (Krelling et al 2017 ; Ogbuagu et al 2022 ). Ogbuagu et al ( 2022 ) further observed key points for consideration in this discourse: in the saltmarsh-mudflat system of Hythe in Southampton Water, the high retention efficiency of nurdle microplastics (denoted with the pellet morphology in this study) was attributed to the saltmarsh vegetation modulating flow velocity and enhancing sediment accretion, which would in turn limit resuspension of microplastics. Sedimentation rates of organic and anthropogenic material originating from upstream sources, in conjunction with the flood-ebb cycles of the monthly dual spring-neap tides of the study area, may influence the movements of the sediments and result in microplastic accretion over time (NFF 2014 ; Díaz-Jaramillo et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, variability in mp/MeP concentration may be consequent to the dynamic nature of estuaries, with the influence of tidal fluctuations, water circulation patterns, infauna burrowing activity, shoreline topography, pollution events and frequencies that may regulate the resuspension, dispersion and settling of plastics (Krelling et al 2017 ; Ogbuagu et al 2022 ). Ogbuagu et al ( 2022 ) further observed key points for consideration in this discourse: in the saltmarsh-mudflat system of Hythe in Southampton Water, the high retention efficiency of nurdle microplastics (denoted with the pellet morphology in this study) was attributed to the saltmarsh vegetation modulating flow velocity and enhancing sediment accretion, which would in turn limit resuspension of microplastics. Sedimentation rates of organic and anthropogenic material originating from upstream sources, in conjunction with the flood-ebb cycles of the monthly dual spring-neap tides of the study area, may influence the movements of the sediments and result in microplastic accretion over time (NFF 2014 ; Díaz-Jaramillo et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surface horizons, though shallower than the sub-surface, retained much higher proportions of loose microplastics and mesoplastics than below, and this may suggest the occurrence of recent pollution events. Microplastics and mesoplastics retained in the sub-surface horizons up to 8 cm had retention influences from several probable trapping variables: shoreline vegetation comprising mostly S. maritimus , P. australis , J. gerardii , A. pungens and A. hastata influence the sediment accretion (and ultimately, the accumulation of microplastics within) along the Chessel Bay intertidal zone; burrowing and foraging activity by fauna such as the crab Carcinus maenas (Ogbuagu et al 2022 ) and birds like the oystercatcher ( Haematopus ostralegus ) and the turnstone ( Arenaria interpres ) may further distribute the microplastics deeper into the sediment profile. Lourenço et al ( 2017 ) acknowledged the redeposition of microplastics by shorebird faeces to tidal flats of estuarine regions in Portugal, Mauritania and Guinea-Bissau.…”
Section: Discussionmentioning
confidence: 99%